A note on the magnetic spherical pendulum - Sierra Porta, David; Montiel, Germain (Ciencia)
The magnetic spherical pendulum is a mechanical system consisting of a pendulum whereof the bob is electrically charged, moving under the influence of gravitation and the magnetic field induced by a magnetic monopole deposited at the origin. Physically not directly realizable, it turns out to be equivalent to a reduction of the Lagrange top. This work is essentially the log book of our attempts at understanding the simplest contemporary approaches to the magnetic spherical pendulum.